A Personal Narrative Experience of Teachers Teaching Purposive Commu-nication During the New Normal Education - Salendab, Fahad Abdul; Akmad, Saiden Panggo (Future Science / FSH-PH Publications, 2023)
This study explored the teachers’ teaching experiences in purposive communication during the new normal education setup at Sultan Kudarat State University-Kalamansig Campus. Qualitative research design using the narrative research methods was the research design of this study. It used non-probability purposive sampling as the sampling technique. There were five (5) teachers handling purposive communication. Moreover, this study employed a semi-structured interview guide with open-ended questions. The data were analyzed using Colizzi’s thematic analysis. The teachers' experiences teaching purposive communication seem fruitful and efficient for students learning. Classes were conducted using the blended learning approach. Due to internet connectivity issues, Asynchronous was the typical learning mode than synchronous session. Further, the learning assessment was found to be unauthentic because it was conducted using asynchronous mode. Internet connectivity and power interruptions were the greatest challenges ever experienced by the teachers. Their coping mechanism included psychological health and well-being and proactive and approach-oriented application. The use of a personal budget is also included. It is concluded that teachers have issues in lesson planning, classroom management, internet connectivity, and managing students' virtual behavior in the new normal environment. Teachers have utilized a variety of strategies to overcome difficulties. It is recommended that the institution should provide planning programs as a foundation for new normal teaching and perform a series of studies on instructors' experiences in the new normal educational scheme. The faculty should evaluate the practicability of their teaching methods to satisfy the needs of students with diverse cultures during the new normal.